Penerimaan diri dan subjective well-being remaja di Panti Asuhan Kristen/Katolik - Delvianti, Helsya; Aryono, Marcella Mariska (PSYCOMEDIA : Jurnal Psikologi, 2025)
Adolescents living in orphanages face various psychosocial conditions that can affect subjective well-being, such as separation from their families and the demands of adjusting to their environment. Subjective well-being reflects an individual's evaluation of their life, including life satisfaction and positive and negative affective experiences. One internal factor that is theoretically assumed to be related to subjective well-being is self-acceptance. This study aims to examine the relationship between self-acceptance and subjective well-being in adolescents living in Christian/Catholic orphanages. This study uses a quantitative approach with a correlational design involving 60 adolescents selected using total sampling technique. The research instruments consist of a self-acceptance scale and a subjective well-being scale. Data analysis was performed using Pearson's correlation. The results of the analysis show that the relationship between self-acceptance and subjective well-being is not significant. These findings can be interpreted to mean that the subjective well-being of adolescents in orphanages is more influenced by external factors, such as social support from caregivers and peers, interpersonal relationships, and the orphanage environment, than by internal factors such as self-acceptance.